Depressing the hydrogenation and decomposition reaction in H2O2 synthesis by supporting AuPd on oxygen functionalized carbon nanofibers. Issue 3 (9th December 2015) - Villa, Alberto; Freakley, Simon J.; Schiavoni, Marco; Edwards, Jennifer K.; Hammond, Ceri; Veith, Gabriel M.; Wang, Wu; Wang, Di; Prati, Laura; Dimitratos, Nikolaos; Hutchings, Graham J.
Abstract : The introduction of oxygen functionalities to the surface of CNFs depressed the hydrogenation and decomposition reaction during the synthesis of H2 O2 . Abstract : In this work, we show that the introduction of acidic oxygen functionalities to the surface of carbon nanofibers serves to depress the hydrogenation and the decomposition of hydrogen peroxide during the direct synthesis of H2 O2 . Moreover, the presence of acidic groups enhances the H2 O2 productivity in the case of supported AuPd nanoparticles.